2016
DOI: 10.1016/j.heares.2015.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Delayed loss of hearing after hearing preservation cochlear implantation: Human temporal bone pathology and implications for etiology

Abstract: Graphical Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
114
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 142 publications
(118 citation statements)
references
References 37 publications
4
114
0
Order By: Relevance
“…As reported in previous studies (9,10), some ECoG responses showed an increase after insertion of the cochlear implant electrode. In this series, such a finding was present in five subjects (Subjects 4,5,8,12,and 14). Different reasons could be responsible.…”
Section: Discussionsupporting
confidence: 46%
See 2 more Smart Citations
“…As reported in previous studies (9,10), some ECoG responses showed an increase after insertion of the cochlear implant electrode. In this series, such a finding was present in five subjects (Subjects 4,5,8,12,and 14). Different reasons could be responsible.…”
Section: Discussionsupporting
confidence: 46%
“…Besides acute cochlear trauma during surgery, postoperative mechanisms seem to influence hearing preservation. Early inflammatory responses (33) or endolymphatic hydrops (34) could lead to hearing loss during the early postoperative phase, whereas tissue responses (8,35) and excitotoxicity because of electrical stimulation (36) could, among other factors, lead to delayed loss of residual hearing within months. Therefore, to further explore the correlation between trauma during surgery and postoperative hearing loss and gain more insight regarding the incidence of postoperative mechanisms, a tool to assess cochlear trauma during surgery is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of significant correlation between fibrous tissue thickness and word recognition scores may be due to either that fibrous encapsulation of the electrode is not an important determinant factor, or that given the small sample size, there is insufficient data to demonstrate a significant effect. Although fibrous tissue thickness does not correlate with CI performance, fibrosis within the cochlea may play a role in loss of residual acoustic hearing with cochlear implantation (Quesnel et al, 2016, Bas et al, 2016). Therefore, understanding the etiology of fibrous capsule development may influence electrode array design as the indications for cochlear implantation expand to include those with more residual hearing.…”
Section: Discussionmentioning
confidence: 99%
“…This finding demonstrates that delayed hearing loss in the low frequencies is not caused by the degeneration of spiral ganglia neurons. Recently, a single case of human temporal bone study was published of a patient who had received the Iowa/Nucleus8 hybrid implant electrode (16). This patient experienced progression of loss of residual hearing and at18 weeks following surgery he had profound sensorineural hearing loss in the operated ear.…”
Section: Discussionmentioning
confidence: 99%